Morphogen and proinflammatory cytokine release kinetics from PRGF‐Endoret fibrin scaffolds: Evaluation of the effect of leukocyte inclusion. Issue 3 (12th June 2014) - Anitua, E.; Zalduendo, M. M.; Prado, R.; Alkhraisat, M. H.; Orive, G.
Abstract The potential influence of leukocyte incorporation in the kinetic release of growth factors from platelet‐rich plasma (PRP) may explain the conflicting efficiency of leukocyte platelet‐rich plasma (L‐PRP) scaffolds in tissue regeneration. To assess this hypothesis, leukocyte‐free (PRGF‐Endoret) and L‐PRP fibrin scaffolds were prepared, and both morphogen and proinflammatory cytokine release kinetics were analyzed. Clots were incubated with culture medium to monitor protein release over 8 days. Furthermore, the different fibrin scaffolds were morphologically characterized. Results show that leukocyte‐free fibrin matrices were homogenous while leukocyte‐containing ones were heterogeneous, loose and cellular. Leukocyte incorporation produced a significant increase in the contents of proinflammatory cytokines interleukin (IL)‐1β and IL‐16 but not in the platelet‐derived growth factors release (<1.5‐fold). Surprisingly, the availability of vascular endothelial growth factor suffered an important decrease after 3 days of incubation in the case of L‐PRP matrices. While the release of proinflammatory cytokines was almost absent or very low from PRGF‐Endoret, the inclusion of leukocytes induced a major increase in these cytokines, which was characterized by the presence of a latent period. The PRGF‐Endoret matrices were stable during the 8 days of incubation. The inclusion of leukocytes alters the growth factors release profile and also increased the dose of proinflammatory cytokines. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1011–1020, 2015.